PENGARUH LINGKUNGAN KERJA DAN KESEHATAN KESELAMATAN (K3) TERHADAP PRODUKTIVITAS KERJA (STUDI PADA PEKERJA BAGIAN PRODUKSI PT ANEKA INTI PERSADA TELUK SIAK) - Puput Retta Desi; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of work safety health (K3) partially and simultaneously.  This study uses a questionnaire as a tool for collecting data distributed to 60 respondents to the workers for the production of PT Aneka Inti Persada Teluk Siak.  The data is then processed using descriptive analysis and statistical analysis using SPSS 16.0 by conducting validity test, reliability test, simple linear regression analysis, multiple linear analysis, analysis determination (R2) and hypothesis testing by testing t test (partial) and F test  (simultaneous) .The results showed that the first hypothesis testing was work environment on work productivity  tcount (13,269) > ttable (2,320), meaning that the working environment has a significant effect on work productivity.  Second,  work safety health (K3) is tcount (10,481) > ttable  (2,663), meaning that the work environment has a significant effect on work productivity. The results of the Fcount (149,556) > Ftable (3,169), meaning that work environment and work safety health (K3) have a significant effect on work productivity.  Keywords: Work Environment,  Work Safety Health (K3), Work Productivity